Knowledge and Practice of Screening Methods Regarding Breast Carcinoma Among Reproductive-Aged Women - Chhetri, Mamta; Chettri, Muni Raj; Paudel, Amrita; Koirala, Subash; Subedi, Moni; Shrestha, Sumnima (Journal of Karnali Academy of Health Sciences, 2021)
Background: Breast cancer is a major public health problem in developing countries. Breast cancer is the second most common malignancy among Nepalese women. This study aimed to assess the level of knowledge and practice of screening methods of breast carcinoma among reproductive-aged women in Bharatpur Metropolitan city ward no 5.Methods: A Community-based cross-sectional study was conducted from September 17, 2021, to October 16, 2021, using face-to-face interviews in Bharatpur Metropolitan city ward no. 5. A total of 155 reproductive-aged women (15-49 years) were considered as a sample. We used Pearson's Chi-square test and binary logistic regression analysis to assess the factors influencing the knowledge and practice of screening methods of breast carcinoma among reproductive-aged women in Bharatpur Metropolitan City, ward no.5, Chitwan.Results: Among 155 reproductive-aged women, 58.7% had a satisfactory level of knowledge and 41.3% had an unsatisfactory level. 34.2% of respondents knew about screening methods. Respondents acquainted with screening methods were 34.2%. Among them, 60.3% knew about Breast Self Examination (BSE), 52.8% knew about the clinical breast examination (CBE) and 39.6% knew about mammography. The level of knowledge of breast carcinoma was significantly associated with occupation [other than agriculture; Crude odds ratio (COR=2.19; CI=1.10-4.33)], educational status [literate (COR=4.38; CI=1.47-13.10)], marital status [other than married (COR=4.67; CI=1.30-16.68)], monthly income [>40,000 Rs (COR=3.71; CI=1.43-9.62)].Conclusions: More than half of respondents had a satisfactory level of knowledge regarding breast cancer despite that only a few participants had practiced screening methods. Increasing the literacy rate, improving socioeconomic status would increase knowledge and practice of screening methods regarding breast carcinoma. It is needed to provide comprehensive, updated information and supportive interventions which could aim to increase knowledge and practice of screening methods for breast cancer.